Game Application as Teaching Tool to Assist Mastering Installation of Three-Phase Motor Control Topic: Expert Perception - Kamarudin, Muhammad Amirul; Mukred, Jameel Abdulla Ahmed; Sri Sumarwati; Abdullah, Nurhanim Saadah (Online Journal for TVET Practitioners, 2023)
The learning and teaching process using conventional methods might cause students to be unable to highlight their true potential. Besides, it can be more difficult for teachers to choose the types of games that suit the curriculum and students’ needs. Hence, this study aims to develop a game application as a teaching assistant tool for a three-phase direct online starter topic in Electrical Technology Malaysian Vocational Certificate subject for Vocational College students using the Android platform. Learning materials and games are developed using multimedia and interactive elements to attract students to be active in using the learning medium based on game applications as 21st-century learning tools. The development purpose of the game application is to give early exposure to students to the installation of three-phase motor control before going through the laboratory session. The behaviorism learning theory and Game development Life Cycle (GDLC) model, were implemented in the game application development in this research. The researcher used Unity 3D software is online software such as Canva and Microsoft PowerPoint design tools interactively to make a game-based learning application for the three-phase motor control installation subject. Based on the analysis of the findings, the experts agreed that the functionality of this three-phase Motor Control game application can be used well and is suitable to be used as a teaching aid. In addition, these research results can be used by teachers to increase students’ interest and further make the learning process more interesting to improve student understanding.